Heatwaves Similar to the Unprecedented One in Summer 2021 Over Western North America Are Projected to Become More Frequent in a Warmer World - Zizhen Dong; Lin Wang; Peiqiang Xu; Jie Cao; Ruowen Yang (Earth's Future, 2023)
Abstract Western North America (WNA) experienced an unprecedented heatwave from late June to early July 2021, which lies far outside the historical range. Based on the model outputs from Coupled Model Intercomparison Project Phase 6, we find that the likelihood of a heatwave over WNA similar to the 2021 one increases with global warming. Such a heatwave is projected to occur more frequently with increased extreme temperature and shortened return period. It means that a rare event in the current climate will be a more common event in a warmer climate, especially under a high‐emission scenario like the Shared Socioeconomic Pathways 585 (SSP5‐8.5). Moreover, we show a large expansion of areas over WNA that will break the 2021 record in the future with an increasing level of emission scenario. Nevertheless, some heatwave records west of the Rocky Mountains are still difficult to break, highlighting the specific extremity of the 2021 WNA heatwave.